Study on impact of maternal CD4 count on birth outcomes and mother to child transmission of HIV infection - Nyamagoudar, Anita; S, Mruthyunjaya; Patil, Murugesh; Banapurmath, C. R. (International Journal Of Community Medicine And Public Health, 2017)
Background: To study the effect of antenatal maternal CD4 count on prematurity, low birth weight and vertical transmission among HIV positive pregnant women in settings with increased uptake of exclusive breastfeeding as infant feeding option. Methods: Design of the study was prospective study. 3 hospitals attached to EGPAF PPTCT Centre at Bapuji Child Health Institute, JJM Medical College, Davangere. 50 Mother-baby pairs attending PPTCT centre. Main outcome measures: prematurity, low birth weight, infant feeding option and vertical transmission of HIV in relation to maternal CD4 count. Results: Prematurity rates were 13.6% (3/22) and (3/28) mothers with CD4 cell count below and above 350 cells/mm3 respectively. Low birth weight rates were 36.3% (8/22) and 35.7% (10/28) mothers with CD4 cell count below and above 350 cells/mm3 respectively. Vertical transmission of HIV was 3.6 % (1/28) and 4.5% (1/22) among mothers with CD4 count above and below 350cells/mm3 respectively. There was no statistically significant association between low maternal CD4 count and adverse birth outcomes and also vertical transmission of HIV. Mothers opting for exclusive breastfeeding were 100% (22/22) and 82.1% (23/28) with CD4 cell count below and above 350 cells/mm3 respectively (p 0.04). At the same time, rates of vertical transmission did not vary between the two groups of mothers (p 0.86). Conclusions: Low maternal CD4 count did not affect birth outcomes and vertical transmission of HIV. Mother-to-child transmission of HIV remained below <5% while significantly increasing number of mothers took up breastfeeding as infant feeding option.